Phytosphingosine induces systemic acquired resistance through activation of sphingosine kinase. (30th September 2021) - Seo, So Yeon; Kim, Yu Jung; Kim, Jinwoo; Nam, Myung Hee; Park, Ky Young
Abstract: Phytosphingosine (PHS) is a naturally occurring bioactive sphingolipid molecule. Intermediates such as sphingolipid long‐chain bases (LCBs) in sphingolipid biosynthesis have been shown to have important roles as signaling molecules. PHS treatment caused rapid cell damage and upregulated the generation of reactive oxygen species (ROS) and ethylene in tobacco plants. These events were followed by the induction of sphingosine kinase (SphK) in a biphasic manner, which metabolized PHS to phytosphingosine‐1‐phosphate (PHS‐1‐P). On the other hand, a PHS treatment with a virulent pathogen, Phytophthora parasitica var. nicotianae ( Ppn ), alleviated the pathogen‐induced cell damage and reduced the growth of Ppn . A Ppn infection increased the PHS and PHS‐1‐P levels significantly in the upper part of the leaves at the infection site at the later stage. In addition, Ppn increased the transcription levels of serine palmitoyltransferase ( LCB1 and LCB2 ) for sphingolipid biosynthesis at the later stage, which was enhanced further by PHS. Moreover, the PHS treatment increased the transcription and activity of SphK, which was accompanied by prominent increases in the transcription levels of ROS‐detoxifying enzymes and PR proteins in the later phase of the pathogen infection. Overall, the PHS‐induced resistant effects were prominent during the necrotic stage of this hemibiotrophic infection, indicating that it is more beneficial for inhibiting the pathogenicity on necrotic cell death. Phosphorylated LCBs reduced the pathogen‐induced cell damage significantly in this stage. These results suggest that the selective channeling of sphingolipids into phosphorylated forms has a pro‐survival effect on plant immunity. Abstract :